Influence of cockle shell ash and lime on geotechnical properties of expansive clay soil stabilized at optimum silica fume content - Muhammad Syamsul Imran, Zaini; Muzamir, Hasan; Suwito, Anang Rustanto; Hyodo, Masayuki (Trans Tech Publications, 2025)
The study investigates the strength improvement of kaolinite clay soil with the inclusion of various percentages and combinations of silica fume (SF) and cockle shell ash (CKSA). Hence, the mechanical properties of various mix ratios of SF and CKSA are examined through the standard Proctor, unconfined compressive strength (UCS), and consolidated isotropic undrained (CIU) triaxial tests. The samples were treated for 1, 7, 14 and 30 days and examined under the UCS tests. The experimental results show that the strength of the kaolinite clay significantly rises with the inclusion of SF and CKSA at dissimilar mix ratios and curing days. The Field Emission Scanning Electron Microscopy (FESEM) profile has illustrated that the kaolinite clay soil molecules were fused jointly with SF and CKSA to form calcium aluminate hydrates (CAH) and calcium silicate hydrate (CSH), which enhanced the development of strength of the stabilized kaolinite clay. The combination of SF and CKSA resulted in a significant strength increment of the kaolinite clay soil up to 86.99%.